Learning end-of-life care within a constructivist model: Undergraduate nursing students' experiences - Anna E. van der Wath; Pieter H. du Toit (AOSIS, 2015)
Background: Although nursing education aims to equip nursing students to provide care to dying patients and their families, nurses often feel ill-prepared to cope with the emotional labour involved in end-of-life care. Objectives: The aim of the study was to explore and describe nursing students' experiences of end-of-life care through experiential learning within a constructivist educational model. Method: A qualitative, descriptive design was used. As part of introducing experiential learning, innovative educational practices were initiated during a second year level undergraduate nursing module on end-of-life care. Qualitative data on second-year nursing students' experiences were collected through written reflections and analysed using open coding. Results: The themes that emerged revealed participants' sensory and emotional experiences during the learning opportunities. Participants reflected on what they learnt and clarified their values related to death and dying. They indicated how they would apply the new meanings constructed in clinical practice. Conclusion: A constructivist educational model of experiential learning holds potential to enhance value clarification and nursing students' sensory and emotional awareness of death and dying. Experiential learning is recommended to develop nursing students' competency inproviding end-of-life care.